- #1

- 53

- 8

## Homework Statement

Find roots of

$$

-\lambda ^3 +(2+2i)\lambda^2-3i\lambda-(1-i) = 0

$$

## Homework Equations

## The Attempt at a Solution

I tried my old trick

I tried to separating the 4 terms into 2 pairs and try to find a common factor in the form of ##\lambda + z## between them,

$$

-\lambda ^2 (\lambda -2-2i) - 3i\lambda -1+i

$$

It doesn't seem to work.

$$

-\lambda (\lambda^2 +3i) - (2+2i)\lambda -1+i

$$

Nope.

And I am out of tricks.

Should I keep trying to factorize it or there is something else I should do about polynomial with complex coefficient?